The European Monetary Union and the Regional Inequalities - Trifon Kostopoulos (European Regional Science Association (ERSA), 2003)
In this paper there will be made an attempt for a comparative political and economic evaluation of the European Monetary Union with the criterionof regional inequalities of the European Union. The national and the regional inequalities of the European Union will be analyzed under the framework of the policies of the European Monetary Union. Initially we will examine the regional dimension of the european unification on the basis of the European Union with 15 member-states(EU15).As criteria we select the different levels of economic development of the member-states examining the regional inequalities on a national level.On this basis we observ that the member states converge creating the "hard core of Europe" and the member states diverge from the average level of the development of the European Union determining the countries of "community cohesion". Next we apply the previous criteria to the EU27, in other words it is useful to research the inequalities of the levels of economic development, which result in the European Union, if all the other candidate countries would be able to be taken within the EU of 15 as is today.In the EU of 27 with the basis of per capita GNP exist three groups of countries instead of two as exist today. The first group consists of the present member states of the E15,except for Spain,Greece and Portugal of which the GNP per capita exceeds by 20% the new weighted average of the EU27. the second group consists of the present member states of community cohesion ,i.e. Spain greece and Portugal plus Cyprus,Czechia,and Malta with per capita GNP between 68%(Czechia)and 95%(Spain) of the averege of the EU27. The third group consists of the remaining eight candidate countries with GNP per capita below 40% of the average of the EU27,with the exemption of Slovakia and Hungaria of which the GNP per capita lies between 56%-58% of the average of the EU27. Therefore,the expected expansion with the complex inequalities will result in a big challenge for the European regional policy, and the policy of the economic and social cohesion. First,the expansion will more than double the population of the European Union that lives in regions with GNP per capita below of the 75%of the present average of the EU.This number will raise from 71 million at the present to 174 million of people or different stated from 19% of the total of 15 to 36% of the total of EU27. Second the scale and the size of regional inequalities will be increased. Therefore in 1998 for the less development regions of the EU 15 the per capita GNP was on average 65%of the average of the EU15.With the expansion the GNP per capita of the less development regions of the candidate countries was on the 37% of the average of EU15. Therefore, the co-existence of the poor and rich regions within the eu 27 will make the regional inequalities more complex in this part of the Union which consists of poor countries.We make possibly find ourselves in a new allocation of poverty. Finally,we will attempt to achieve the necessary interventions between the EU15 and the EU27, researching the modern problems of the EU under the expected expansion of the European Union.
Keywords: 330